Spargana infection in frogs of genus Pristimantis (Anura, Strabomantidae) from Peru - Gomez-Puerta, Luis A. (2010)
In this study, we report the parasitism by sparganum of tapeworm Spirometra sp. in amphibians: Pristimantis nephophilus and Pristimantis rhodostichus, from the department of San Martin, Peru. We collected three filiform structures located at the subcutaneous and identified as sparganum. The finding of this metacestode is the first record in amphibians of Peru, and shows that frogs P. nephophilus and P. rhodostichus are new intermediate hosts for Spirometra sp.